Voice assistants as gatekeepers for consumption? How information intermediaries shape competition - Victoriia Noskova (Technische Universität Ilmenau, Institut für Volkswirtschaftslehre, 2021)
In December 2020, new regulation of digital markets was proposed by European Commission. It specifically addresses main concerns raised by business behavior of operators of core services in their gatekeeping positions. However, voice assistants (or digital personal assistants, DPAs, e.g. Apple's Siri, Amazon's Alexa, Google Assistant) are not included into this regulation. In contrast, the Internal Market and Consumer Protection Committee of European Parliament suggested to include them. This paper argues that (i) voice assistants as gatekeepers for consumption should be listed among core services, (ii) some Digital Market Act's obligations need to be adopted to fit specifics of voice assistants, (iii) two relevant dimensions of power should be included into rebuttable presumptions used for competition policy and regulation: market power on voice assistants' market and ecosystem of related markets (cross-market integration criterion), (iv) growth of new gatekeepers should be prevented, among other means by stricter merger control.
Keywords: K21; L1; L4; L86; O33; D4; 330; Voice Assistants; Gatekeepers; Digital Market Act; Digital Personal Assistants; Virtual Assistants; Competition in Digital Markets; Competitive Bottleneck; Information Intermediaries; Platform Competition; Smart Speakers; Siri; Alexa; Google Assistant